(untitled) (Zaporizhzhia Historical Review, 2021)
In historiography is presented plenty of the scientific studies in which the questions of history of city selfgovernment were raised, but modern historians yet have many perspective directions of scientific research of the problem. In particular, specifity and regularities in the development of Ukrainian self-government in the context of Western Europe and determination of regional introduction of the Magdeburg right in different regions of Ukraine require more detailed study.